Risk Factors For Musculoskeletal Complaints AmongFlower Board Craftsmen in Jember City - Aprilia Nurma Firdausi; Ragil Ismi Hartanti; Noeroel Widajati; Dakwatun Shofia (Tadulako University, 2026)
The musculoskeletal system plays an important role in carrying out daily activities to increase work productivity. However, musculoskeletal complaints are still common, especially in the informal sector, which have an impact on work accidents and decreased work productivity. This study aims to assess the risk of work posture and factors related to both individuals and work on musculoskeletal complaints. This type of research is a analytic cross-sectional study with descriptive and correlational analysis. It was conducted on 8 florists producing flower boards with a sample of 31 flower board craftsmen. Data collection methods were carried out through interviews and observations, using a questionnaire on respondent characteristics, Rapid Entire Body Assessment (REBA) to measure work posture, and Nordic Body Map (NBM) to assess MSDs complaints. The results showed that almost all flower board craftsmen experienced MSDs complaints with the most common level of complaints being moderate at 45.2%. There is a relationship between individual factors (age, smoking habits, years of service, and BMI) and work factors (work posture) with MSDs complaints. However, there is no relationship between individual factors (gender, exercise habits, and length of working) and work factors (work stage) with MSDs complaints. It was concluded that the risk factors for MSDs complaints in flower board craftsmen in Jember city were age, smoking habits, years of service, BMI, and work posture